Chemical fixation of CO2 into cyclic carbonates catalyzed by bimetal mixed MOFs: the role of the interaction between Co and Zn. Issue 2 (29th November 2019) - Wu, Yuanfeng; Song, Xianghai; Xu, Siquan; Chen, Yuan; Oderinde, Olayinka; Gao, Lijing; Wei, Ruiping; Xiao, Guomin
Abstract : Catalytic conversion of carbon dioxide into cyclic carbonates in the presence of bimetal mixed MOFs. Abstract : Bimetal mixed MOFs of [CoZn][(BDC)(DABCO)0.5 ] (CZ-BDO), [CoNi][(BDC)(DABCO)0.5 ] (CN-BDO), and [NiZn][(BDC)(DABCO)0.5 ] (NZ-BDO) were prepared under solvothermal conditions and further employed as highly active accelerants for converting carbon dioxide into cyclic carbonates. The characteristics of the bimetal compounds were revealed via various techniques, including ICP-OES, XRD, FT-IR, Raman, XPS, SEM, EDS maps, N2 adsorption, TG-DTG, and CO2 /NH3 -TPD. The catalytic results revealed that CZ-BDO is superior to the other samples for obtaining a satisfactory chloropropene carbonate (CPC) yield. The excellent catalytic activity may be owing to the presence of a solid solution within the Co and Zn bimetal sample, which provides synergistic catalysis in the carbon dioxide cycloaddition. In addition, the synergistic catalysis was further confirmed by the NH3 -TPD profiles, whereby the amount of CZ-BDO basic sites was obviously enhanced compared to the other samples. Furthermore, DFT calculations were also performed to reveal the synergistic catalysis between Co and Zn for the coupling reaction. Additionally, when the coupling reaction was carried out at 100 °C for 5 h in the presence of 0.5 wt% epichlorohydrin (ECH) as a catalyst at 3.0 MPa, 99.31% conversion of ECH and 97.05% yield of CPC were obtained over the optimal CZ-BDO sample. Moreover, the bimetal sample can also efficiently convert other epoxides into the corresponding cyclic carbonates.